Uso dos recursos tecnológicos nas práticas dos professores dos anos iniciais do ensino fundamental - Cruz, Tatiane Severgnini da (2014)
The integration of technological resources in teaching and learning process assigns to education a need for new thinking and sets new challenges to the routine of the classroom, leaving the teacher to review practices and concepts confront this issue. Given this situation, we conducted a qualitative research, as Lüdke and Andrew (1986) through a case study in a public school in the city of São Carlos - SP, with two active teachers in elementary education from the early years, with in order to answer the following question: What ideas have influenced the organization of pedagogical practices with technological resources of teachers in the early years of elementary school? Data were grouped into two angles: 1) the design of technological resources for teachers; and 2) Characterization of teaching practices with the use of technological resources. Our analyzes received theoretical background , mainly from Maurice Tardif , Maria Luiza Belloni , Vani Kenski Moreira , Vieira Pinto , Lion , Bernadette Gatti , Marcelo Garcia. Generally the teachers investigated using resources such as radio and television, which are dominated by them. Resources such as computers and data projectors are used by teachers with more fear; since these are equipments that they do not dominate. These and other aspects lead us to realize the importance of training teachers to use technological resources in a way that leverages the educational process, promoting student learning. Yet conducted a bibliographic study on digital database of thesis and dissertations to articulate the data found by analyzing the concepts and practices of the two teachers.